Performance overhead comparison between hypervisor and container based virtualization - Li, Zheng; Kihl, Maria; Lu, Qinghua; Andersson, Jens A. (31st IEEE International Conference on Advanced Information Networking and Applications, AINA 2017, Taipei, Taiwan, 2017-03-27 - 2017-03-29, 2017)
The current virtualization solution in the Cloud widely relies on hypervisor-based technologies. Along with the recent popularity of Docker, the container-based virtualization starts receiving more attention for being a promising alternative. Since both of the virtualization solutions are not resource-free, their performance overheads would lead to negative impacts on the quality of Cloud services. To help fundamentally understand the performance difference between these two types of virtualization solutions, we use a physical machine with 'just-enough' resource as a baseline to investigate the performance overhead of a standalone Docker container against a standalone virtual machine (VM). With findings contrary to the related work, our evaluation results show that the virtualization's performance overhead could vary not only on a feature-by-feature basis but also on a job-to-job basis. Although the container-based solution is undoubtedly lightweight, the hypervisor-based technology does not come with higher performance overhead in every case. For example, Docker containers particularly exhibit lower QoS in terms of storage transaction speed.
Keywords: Cloud Service; Container; Hypervisor; Performance Overhead; Virtualization Technology